Stigmasterol alleviates interleukin-1beta-induced chondrocyte injury by down-regulatingsterol regulatory element binding transcription factor 2 to regulateferroptosis. Issue 2 (20th December 2021) - Mo, Zhisheng; Xu, Peiqing; Li, Huanyu
ABSTRACT: Stigmasterol (STM), one of the main active components of Achyranthes bidentata, has been shown to effectively inhibit proinflammatory factors and matrix degradation in chondrocytes. However, the effect of STM on interleukin (IL)-1β-induced chondrocytes and its specific mechanism remain unclear. The purpose of the present study was to explore the effect and mechanism of sterol regulatory element binding transcription factor 2 (SREBF2) on IL-1β induced chondrocytes in the presence of STM. CCK-8 was used to detect the effect of STM on the cell viability of mouse chondrogenic cells (ATDC5). After ATDC5 cells were induced by IL-1β, the expression of SREBF2 in osteoarthritis cells was detected by RT-qPCR. The content of iron ion in the cells was detected by using an iron colorimetric assay kit. After further transfection of a SREBF2 overexpressing vector (Oe-SREBF2) or addition of a ferroptosis inhibitor, the expression levels of inflammation and matrix degradation-related proteins were detected via Western blotting. The levels of oxidative stress in cells were determined by using an ELISA kit. The results revealed that STM had no significant effect on the viability of ATDC5 cells. STM reduced IL-1β-induced ATDC5 cell damage and ferroptosis through SREBF2 and enhanced the inhibitory effect of ferroptosis inhibitors on IL-1β-induced ATDC5 cell injury. The present data suggest that STM attenuated chondrocyte injury induced by IL-1β by regulating ferroptosis via down-regulation of SREBF2, and may have potential as a novel therapeutic method for knee osteoarthritis.